PENGARUH PARTISIPASI MASYARAKAT, PERAN PERANGKAT DESA DAN KOMPETENSI PERANGKAT DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Chalista Rambu Olivia; Rochmad Bayu Utomo; Andi Hidayatul Fadlilah (LPPM Universitas Ibnu Sina, 2023)
The goal of this research was to determine whether or not village officials are held accountable for the proper use of village funds, and whether or not they have the necessary skills to do so. It is hoped that the findings of this research would provide useful information to village leaders and the general public on the administration of local finances. Participants in the evolution of village fund management constitute the study population. Community leaders that regularly participate in the Village Development Planning Meeting were used as the sample. This research used a purposive sampling strategy. Primary data in the form of fifty completed questionnaires was employed. Multiple linear regression analysis was utilized to analyze the data, and the findings indicated that 1) village budget management accountability is significantly improved by public involvement. 2) The accountability of village finance management is significantly impacted by the involvement of village authorities. Thirdly, the accountability of village money management is significantly affected by the competency of village administrators.